Technologies of Work of the Social Teacher with gifted children (Journal of Educational Sciences, 2018)
The technology and work of the social teacher with gifted children is considered in the articlе The giftedness is a special quality of the person transferred from the birth and abilities of the person with versatility of giftedness. In pedagogics «giftedness» is understood as extensiveness of human opportunities, as the general abilities defining efficiency of activity, intellectual potentials, informative opportunities of training and integrity of abilities and also talent of the person from the birth. In this regard the author analyzing definitions «giftedness» gives an explanation to such types of giftedness as intellectual, academic, art, creative, sports, leader and social. In this article the giftedness is considered as one of types of deviations therefore it is characterized features of work of the social teacher. Thedetermination ways of children giftedness, types of works with parents of gifted children, consultation ethics, special questionnaires and psychodiagnostic trainings reveal. The author offers examples of exercises and tasks which he is used for development of memory of giftedness children, makes recommendations about their performance.Key words: giftedness, opportunity, ability, social teacher, deviation, intelligence of mind, feature of children.